FragHAR: towards ab initio quantumcrystallographic X-ray structure refinement for polypeptides and proteins. (2020) - Bergmann, Justin; Davidson, Max; Oksanen, Esko; Ryde, Ulf; Jayatilaka, Dylan
No abstract available